DEVELOPMENT AND VALIDATION OF FIRST ORDER DERIVATIVE SPECTROPHOTOMETRIC METHOD FOR ESTIMATION OF LACOSAMIDE IN BULK AND TABLET DOSAGE FORM - CHAUDHARI, RAJESHRI D.; CHOKSI, VISHRUTI H.; DIVAN, TANVI; PATEL, BHAVNA A.; PARMAR, SHRADDHA J. (Asian Journal of Pharmaceutical and Clinical Research, 2013)
ABSTRACT: To develop a simple, precise, accurate and reproducible spectrophotometry method for estimation of Lacosamide by employing first order derivative method and validate it as per ICH guidelines. The method is based on first order UV derivative spectrophotometry. Distilled water was selected as a solvent for estimation of Lacosamide with the absorption at 250 nm for quantification of Lacosamide. The linearity was established over the concentration range of 5-50 Âµg/ml for Lacosamide. The correlation coefficient (r2) for Lacosamide was 0.9980. The mean % recovery was found to be in range of 99.24% - 99.72% for Lacosamide. The results of analysis have been validated statistically and recovery studies confirmed the accuracy of the proposed method. The method was validated as per the International Conference on Harmonization (ICH) guidelines. The proposed method is recommended for routine analysis since it is rapid, simple, accurate, sensitive and specific. Key words: Lacosamide, Spectrophotometry, First order derivative,